Local gastric RAAS inhibition improves gastric microvascular perfusion in dogs. Issue 3 (June 2019) - Truse, Richard; Voß, Fabian; Herminghaus, Anna; Schulz, Jan; Weber, Andreas P M; Mettler-Altmann, Tabea; Bauer, Inge; Picker, Olaf; Vollmer, Christian
Abstract : During circulatory shock, gastrointestinal microcirculation is impaired, especially via activation of the renin-angiotensin-aldosterone system. Therefore, inhibition of the renin-angiotensin-aldosterone system might be beneficial in maintaining splanchnic microcirculation. The aim of this study was to analyze whether locally applied losartan influences gastric mucosal perfusion (µflow, µvelo) and oxygenation (µHbO2 ) without systemic hemodynamic changes. In repetitive experiments six anesthetized dogs received 30 mg losartan topically on the oral and gastric mucosa during normovolemia and hemorrhage (−20% blood volume). Microcirculatory variables were measured with reflectance spectrometry, laser Doppler flowmetry and incident dark field imaging. Transpulmonary thermodilution and pulse contour analysis were used to measure systemic hemodynamic variables. Gastric barrier function was assessed via differential absorption of inert sugars. During normovolemia, losartan increased gastric µflow from 99 ± 6 aU to 147 ± 17 aU and µvelo from 17 ± 1 aU to 19 ± 1 aU. During hemorrhage, losartan did not improve µflow. µvelo decreased from 17 ± 1 aU to 14 ± 1 aU in the control group. Application of losartan did not significantly alter µvelo (16 ± 1 aU) compared to the control group and to baseline levels (17 ± 1 aU). No effects of topical losartan on macrohemodynamic variables or microcirculatory oxygenation were detected. Gastric microcirculatory perfusion is at least partly regulated by local angiotensin receptors. Topical application of losartan improves local perfusion via vasodilation without significant effects on systemic hemodynamics. During mild hemorrhage losartan had minor effects on regional perfusion, probably because of a pronounced upstream vasoconstriction.